2021
DOI: 10.1371/journal.pone.0246619
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of gastritis among patients visiting Saint Paul Hospital Millennium Medical College, Addis Ababa, Ethiopia

Abstract: Background The health of individuals is not only the absence of disease checked medically, but also encompasses social and psychological aspects. Any departure from the state of physiological, psychological, or social well-being was affected by different factors. However, all contributory factors were not equally responsible for affecting disease. This study was undertaken as a search for the relative effects of sociocultural and individual behavioral factors contributing to acute and chronic gastritis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
1
14
1
7
Order By: Relevance
“…Previous studies have shown that both sexes are susceptible to gastritis and ulcers, followed by chronic gastric cancer, but the results are inconsistent [61][62][63][64]. In our study, we found a significant association between the inflammatory potential of diet and the risk of gastric disease among females.…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have shown that both sexes are susceptible to gastritis and ulcers, followed by chronic gastric cancer, but the results are inconsistent [61][62][63][64]. In our study, we found a significant association between the inflammatory potential of diet and the risk of gastric disease among females.…”
Section: Discussioncontrasting
confidence: 43%
“…The gender differs from literature's data. Some studies such as those conducted by Jemilou AC et al [5] and Feyisa ZT et al [6] showed a female predominance of patients with chronic gastritis. These authors observed that females accounted for 54.7% and 67.6% of cases in their series, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…40 Through a cross-sectional analysis of 364 patients, Feyisa and Woldeamanuel reported that psychological stress could contribute to gastritis (OR: 2.168; 95% CI 1.046 to 2.174). 41 …”
Section: Discussionmentioning
confidence: 99%
“…40 Through a cross-sectional analysis of 364 patients, Feyisa and Woldeamanuel reported that psychological stress could contribute to gastritis (OR: 2.168; 95% CI 1.046 to 2.174). 41 Since long working hours induce work-related psychosocial stress, psychosocial stress could mediate the association between long working hours and gastritis. Considering the proposed mechanisms, further studies should include job stress or stressors in the analysis, to determine whether work-related psychosocial stress mediates the association between long working hours and gastritis.…”
Section: Psychosocial Stress and Gastritismentioning
confidence: 99%